Direct fluorescence imaging of lignocellulosic and suberized cell walls in roots and stems - Kitin, Peter (2021)
Investigating plant structure is fundamental in botanical science and provides crucial knowledge for the theories of plant evolution, ecophysiology and for the biotechnological practices. Modern plant anatomy often targets the formation, localization and characterization of cellulosic, lignified or suberized cell walls. While classical methods developed in the 1960s are still popular, recent innovations in tissue preparation, fluorescence staining and microscopy equipment offer advantages to the traditional practices for investigation of the complex lignocellulosic walls. Our goal is to enhance the productivity and quality of microscopy work by focusing on quick and cost-effective preparation of thick sections or plant specimen surfaces and efficient use of direct fluorescent stains. We discuss popular histochemical microscopy techniques for visualization of cell walls, such as autofluorescence or staining with calcofluor, Congo red (CR), fluorol yellow (FY) and safranin, and provide detailed descriptions of our own approaches and protocols. Autofluorescence of lignin in combination with CR and FY staining can clearly differentiate between lignified, suberized and unlignified cell walls in root and stem tissues. Glycerol can serve as an effective clearing medium as well as the carrier of FY for staining of suberin and lipids allowing for observation of thick histological preparations. Three-dimensional (3D) imaging of all cell types together with chemical information by wide-field fluorescence or confocal laser scanning microscopy (CLSM) was achieved.